2021
DOI: 10.1111/ijal.12375
|View full text |Cite
|
Sign up to set email alerts
|

The motivation‐anxiety interface in language learning: A regulatory focus perspective

Abstract: The study examined the relationship between chronic regulatory focus, L2 self‐guides, L2 anxiety, and motivated behavior. Questionnaire data were collected from 161 English learners in a foreign language context. Multiple regression results showed that the participants’ promotion focus (concerned with accomplishments and achievements) strongly and negatively predicted their L2 anxiety whereas their prevention focus (concerned with safety and obligations) was unrelated to L2 anxiety. Additionally, ought L2 self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 50 publications
2
19
1
Order By: Relevance
“…Two studies have directly employed the regulatory focus theory. Jiang and Papi (2021) found that a promotion focus negatively predicts L2 speaking anxiety among Chinese learners of English. In Iran, Papi and Khajavy (2021) found that a promotion focus positively predicted ideal L2 selves, which in turn contributed to the emotion of L2 enjoyment, an eager L2 use inclination, and L2 achievement.…”
Section: Regulatory Focus Theorymentioning
confidence: 98%
See 1 more Smart Citation
“…Two studies have directly employed the regulatory focus theory. Jiang and Papi (2021) found that a promotion focus negatively predicts L2 speaking anxiety among Chinese learners of English. In Iran, Papi and Khajavy (2021) found that a promotion focus positively predicted ideal L2 selves, which in turn contributed to the emotion of L2 enjoyment, an eager L2 use inclination, and L2 achievement.…”
Section: Regulatory Focus Theorymentioning
confidence: 98%
“…L2 learners with a promotion focus are speculated to take advantage of every opportunity they get to use the target language due to their eager strategic inclinations (Papi et al, 2019;Papi and Khajavy, 2021) and risk-taking tendency (Scholer et al, 2010); they may also pursue maximal L2 learning goals (ideal L2 selves) such as advanced proficiency, which could further motivate their eager behaviors contributing to their pragmatic competence. On the other hand, L2 learners with a prevention focus, who are more risk-averse and have vigilant strategic inclinations, are speculated to have lower levels of pragmatic competence due to their tendency to minimize the possibility of making errors by avoiding the unnecessary use of the L2; they are also motivated by minimal goals (ought L2 selves) such as meeting institutional obligations, which further increases their anxiety (Jiang and Papi, 2021;Tahmouresi and Papi, 2021) and dissuades them from using the target language.…”
Section: Regulatory Focus Theorymentioning
confidence: 99%
“…Jin et al (2015) explained that such a contrast might be related to factors such as using different competitiveness scales, study designs, or other intervening variables. Previous research has found that L2 anxiety can be related to learners’ L2 motivation (Jiang & Papi, 2022; Papi, 2010; Papi & Khajavy, 2021; Tahmouresi & Papi, 2021; Teimouri, 2017). Individuals motivated by an ought-to L2 self (representing the learner's L2-related duties and obligations) tend to experience more L2 anxiety in comparison with individuals motivated by an ideal L2 self (representing one's L2-related hopes and aspirations), because the former group is more prevention-focused and sensitive to the presence or absence of negative outcomes, which naturally provoke anxiety.…”
Section: Group 3: Sources Of L2 Anxietymentioning
confidence: 99%
“…Learners’ regulatory focus and regulatory mode have also been found to predict L2 anxiety. Jiang and Papi (2022) found that learners’ regulatory focus and concern with growth and accomplishments strongly and negatively predicted their L2 anxiety. Teimouri et al (2022) found that learners’ regulatory mode of assessment, representing preoccupation with the accuracy and suitability of L2 output, positively predicted their L2 anxiety, whereas their locomotion mode, representing the preoccupation with the act of communication, negatively predicted their L2 anxiety.…”
Section: Group 3: Sources Of L2 Anxietymentioning
confidence: 99%
“…Anxiety is a critical aspect of effect in language learning and plays an imperative role in SLA (Horwitz, 2016 , 2017 ; Oxford, 2017 ; Gregersen, 2020 ; Sudina, 2021 ; Jiang and Papi, 2022 ; Pan et al, 2022 ). In general, foreign language anxiety (FLA) is defined as “a distinct complex construct of self-perceptions, beliefs, feelings, and behaviors related to classroom language learning arising from the uniqueness of language learning process” (Horwitz et al, 1986 , p. 128).…”
Section: Literature Reviewmentioning
confidence: 99%